Effect of Competence, Organizational Climate, Job Satisfaction, Organizational Commitment, Work Discipline, Work Motivation, Leadership Style, and Career Development on Performance Health Service Officers Kutai Barat District - Wisdafiesta Hinuq, Rafaela; Iskandar, Iskandar; Mulyadi, Mus (Journal of World Science, 2022)
Introduction: This study aims to analyze and determine the magnitude of the influence of competence, organizational climate, job satisfaction, organizational commitment, work discipline, work motivation, leadership style, and career development on the performance of the employees of the Health Office of West Kutai Regency partially or simultaneously. Methods: This research is a quantitative study using an associative approach. Research with this associative approach is used to identify the extent to which the independent variable affects the dependent variable. This research was started in early January 2022 to early February 2022 with the research location at the Health Office of West Kutai Regency and the number of samples as many as 49 people. This study uses the SPSS instrument, which discusses validity and reliability testing, multiple linear regression analysis, t-test, F test, and coefficient of determination to determine the extent to which the independent variable contributes to the dependent variable. Results: The results showed that simultaneously the variables of competence (X1), organizational climate (X2), job satisfaction (X3), organizational commitment (X4), work discipline (X5), work motivation (X6), leadership style (X7) and career development (X8) has a positive and significant effect on employee performance (Y) with an influence contribution of 93.5% while the remaining 6.5% is influenced by other variables not included in this study. However, partially, only organizational climate variables (X2) and leadership style (X7) do not affect employee performance at the Health Office of West Kutai Regency. In contrast, the remaining variables are Competence (X1), job satisfaction (X3), organizational commitment (X4), and work discipline (X4). X5), work motivation (X6), and career development (X8) have a positive and significant influence on the performance of the employees of the Health Office of West Kutai Regency.